2020
DOI: 10.3390/sym12122017
|View full text |Cite
|
Sign up to set email alerts
|

New Refinements for the Error Function with Applications in Diffusion Theory

Abstract: In this paper we provide approximations for the error function using the Padé approximation method and the Fourier series method. These approximations have simple forms and acceptable bounds for the absolute error. Then we use them in diffusion theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…With regard to the previous lower and upper bounds of Φx, the common limitation to almost all of them is that they do not show a tight lower and upper bound for all values of the argument x>0. For example, the numerical results in Section 4 of this paper showed that the bounds of Bercu [11] (i.e. normalΦLBEx and normalΦUBEx) are very tight for small values of x, but it is less sharp for large values of x.…”
Section: Overview Of Some Bounds For φXmentioning
confidence: 90%
See 1 more Smart Citation
“…With regard to the previous lower and upper bounds of Φx, the common limitation to almost all of them is that they do not show a tight lower and upper bound for all values of the argument x>0. For example, the numerical results in Section 4 of this paper showed that the bounds of Bercu [11] (i.e. normalΦLBEx and normalΦUBEx) are very tight for small values of x, but it is less sharp for large values of x.…”
Section: Overview Of Some Bounds For φXmentioning
confidence: 90%
“…Bercu [11] gave the following lower and upper bounds for Φx when 0x6.248: normalΦLBExΦxnormalΦUBEx, where normalΦLBEx=12+β1x/2π and normalΦUBEx=12+β2x/2π. Also, β1normalt=110normalt3+210t39normalt4+180normalt2+210 and β2normalt=113400t29t8660t6+1260t4+37800t2+113400. As noted by Bercu [11], the upper bound normalΦUBEx is valid only for 0x6.248. Peric et al [12] suggested a new lower bound for Φx based on the lower bound of Boyd [6] and the lower bound of Ruskai and Werner […”
Section: Overview Of Some Bounds For φXmentioning
confidence: 99%
“…Also, let ℎ 𝐿−𝑡 (𝑥) be the absolute error function between the lower bound of Φ(𝑥) and the exact Φ(𝑥). That is, ℎ 𝑠−𝑡 (𝑥) = |Φ 𝑠−𝑡 (𝑥) − Φ(𝑥)|, where 𝑠 stands for 𝑈 or 𝐿 and 𝑡 stands for 𝑅𝑊 (Roskai and Werner, 2000), 𝐴𝐿 (Alzer, 2010), 𝐴𝐵 (Abreu, 2012), 𝑀𝐽 (Mastin and Jaillet, 2013), 𝑃𝐸 (Peric et al, 2019), 𝐵𝐸 (Bercu, 2020) and 𝐸𝐼 (Proposed bounds as given in Section 3). The absolute error associated with these bounds becomes very small as the size of 𝑥 increases.…”
Section: Numerical Comparisons and Conclusionmentioning
confidence: 99%
“…The Q-function and error function are widely used in Bit Error Rate (BER) analysis of communication systems (see Trigui et al, 2021 and the references theirin). Due to the relationship between Φ(𝑥) and the above functions along with the Mills' ratio (Fan, 2013), it makes sense that the results would find application in the broader fields such as statistical computations, applied statistics, mathematical models in biology, mathematical physics and diffusion theory (see Bercu, 2020 andLipoth et al, 2022). Eidous and Abu-Shareefa (2020) have reviewed 45 approximations for Φ(𝑥) reported in literature from 1945 to 2019.…”
Section: Introductionmentioning
confidence: 99%
“…𝐴𝐵(Abreu, 2012),𝑁𝐸 (Neumann, 2013), 𝑌𝐴(Yang et al, 2018), 𝐵𝐸(Bercu, 2020) and 𝑃𝑂 (Polya, 1949) (see Section 2). The error function for the proposed upper bound is ℎ r~( 𝑥) = Φ r~( 𝑥) − Φ(𝑥) (see Section 3).…”
mentioning
confidence: 99%